(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article describes the technology of a culture of pedagogical communication of primary school teachers; defined conditions, ways, especially the formation of professional communicative competence of primary school teachers.